Differential Source Marking in the languages of Europe - Zaika, Natalia M. (Vilnius University Open Series, 2021)
The article deals with encoding Source arguments of the predicate ‘take’ in the languages of Europe and identifies factors involved in Differential Source Marking. Animacy turns out to play the crucial role in this respect: while the encoding of animate Sources is rather homogeneous, inanimate Sources are encoded in different ways depending on the localization. The encoding of animate source can coincide with that of one of the two (or both) basic localizations: IN or ON or be different from it. Differential Marking of animate Sources is attested in Central Europe and implies recipient-like vs. ablative-like alternation where the encoding depends on whether something is taken for good or not and whether some extra force is applied or not. Differential Marking of inanimate Sources occurs in quite a number of European languages with different localizations; it is not always symmetrical to Differential Translocation Marking and can depend on the topicality on the argument or its semantic type.
Keywords: Source; argument alternation; Differential Argument Marking; languages of Europe; syntax